Interface Engineering for High‐Performance Top‐Gated MoS2 Field‐Effect Transistors. (28th July 2014) - Zou, Xuming; Wang, Jingli; Chiu, Chung‐Hua; Wu, Yun; Xiao, Xiangheng; Jiang, Changzhong; Wu, Wen‐Wei; Mai, Liqiang; Chen, Tangsheng; Li, Jinchai; Ho, Johnny C.; Liao, Lei
<x xml:space="preserve">Abstract</x> Experimental evidence of the optimized interface engineering effects in MoS2 transistors is demonstrated. The MoS2/Y2O3/HfO2 stack offers excellent interface control. Results show that HfO2 layer can be scaled down to 9 nm, yet achieving a near‐ideal sub‐threshold slope (65 mv/dec) and the highest saturation current (526 μA/μm) of any MoS2 transistor reported to date. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>